2018
DOI: 10.1126/science.aar6308
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide membranes with nanoscale Turing structures for water purification

Abstract: The emergence of Turing structures is of fundamental importance, and designing these structures and developing their applications have practical effects in chemistry and biology. We use a facile route based on interfacial polymerization to generate Turing-type polyamide membranes for water purification. Manipulation of shapes by control of reaction conditions enabled the creation of membranes with bubble or tube structures. These membranes exhibit excellent water-salt separation performance that surpasses the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
571
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,206 publications
(622 citation statements)
references
References 34 publications
16
571
0
3
Order By: Relevance
“…Material design using phenomena out of equilibrium, diffusion, and chemical patterns is currently a popular trend in material science since nonequilibrium (NE) phenomena give rise to emergent properties and higher levels of complexity . In a sense, materials formed during NE processes carry the information of the chemical pathway of the NE phenomenon and therefore, have sensing and environment tracking abilities.…”
mentioning
confidence: 99%
“…Material design using phenomena out of equilibrium, diffusion, and chemical patterns is currently a popular trend in material science since nonequilibrium (NE) phenomena give rise to emergent properties and higher levels of complexity . In a sense, materials formed during NE processes carry the information of the chemical pathway of the NE phenomenon and therefore, have sensing and environment tracking abilities.…”
mentioning
confidence: 99%
“…As former characterizations illustrated, the increase in permeation of the NF‐PA‐PPTA/PMIA was far below than that of the supporting membranes because the main resistance of the filtration came from the TFC functional layer, and the TFC functional layer which with rougher and thinner was beneficial for the higher flux. Furthermore, the higher flux of the TFC NF membranes can be obtained if the supporting membranes own a higher flux too 47. Figure 10 (Right) shows the salt retention of the prepared NF membranes, which indicated that the salt retention was in the order of Na 2 SO 4 > MgSO 4 > MgCl 2 > NaCl as common piperazine polyamide TFC NF membranes shown.…”
Section: Resultsmentioning
confidence: 95%
“…The TFC NF membranes with the pure PMIA supporting membrane and PPTA/PMIA 8, PPTA/PMIA 16 supporting membranes showed the typical modular structures mainly resulted from the cross‐linking reaction between the PIP and TMC, and the modular structures distributed uniformly on the top and valley of the CPs and the surface of the substrates. However, it is worth mentioning that both modular structure and Turing Structure 47 were formed on the TFC NF membrane when the PPTA/PMIA 32 membrane used as the substrate. And as clearly shown, the CPs were covered by modular structure and surrounded by Turing Structure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the reaction between organic amine and acid chloride is a typical interfacial polymerization reaction, which is a reaction‐diffusion process far from thermodynamic equilibrium . It is known from our previous studies that the microcapsules still have wrinkles to some degree when there is no fluid flow .…”
Section: Resultsmentioning
confidence: 99%